Bay rāmšahr, a Sasanian Title in the Shahnama - Ahmadreza Qaemmaqami; Amir Arghavan (تاریخ ادبیات)
Scholars are slowly trying to re-edit the Shahnama and in this, they sometimes ask for help from pre-Islamic languages ​​and documents. It is natural to find in the Shahnama reflections of the conditions of the Sassanid era and administrative terms common in that period. In this article, an attempt has been made to identify a Sasanian title, which seems not to have been recognized by the editors, by examining some letters from Sasanian kings or addressed to them, recorded in the Shahnama, in which several titles and epithets are repeated in a formulaic form. For this purpose, it has been tried to check the manuscripts of the Shahnama carefully and to show the origin of the title in the Sasanian documents. This title is “Bay rāmšahr”, recorded in the best editions of the Shahnama, especially in Khaleghi’s edition as “padrām-shahr”. At the end of the discussion, an attempt has been made to prove that “mahast”, which is repeated in the same letters next to “bay rāmšahr”, again in a formulaic form, is nothing but a corruption of the term “mazdēsn”. But this corruption is not from Ferdowsi or the scribes of the Shahnama. This happened most probably long before the composition of the Shahnama in the transmission of Sasanian documents to Arabic and Persian script and with the same form found its way to Abu Mansuri’s and Ferdowsi’s Shahnama.